Agility in an inter-organizational context Investigating inter-organizational cooperation in software companies - Bonnedahl, Johan; Persson, Henry (My University, 2023)
As a response to the fast paced changes required in recent years, agile software de- velopment methods have become increasingly popular. To achieve the increased size and complexity needed for today’s software systems to be competitive, organizations have also started working together. As the number of actors and dependencies in- crease, so does the need for stability and clear structure, which goes against the core values of agility. This thesis examines which conditions are most suitable for the use of agile methods. It also examines which problems are faced by agile organizations working together with other organizations and which solutions could mitigate these problems. This is done through a review of current literature on the subject and through interviews with 11 people working with agile methods in cooperating organizations. Problems are found within 5 key areas: Team autonomy, Communication, Organi- zational alignment, Culture and people, and Flexibility and contracts. The found solutions are to utilize joint teams with people from both organizations to align and evaluate the direction of the work, shorten the communication paths, work contin- uously with integration and foster a sense of unity. The organizations should align and customize their work methods, and continuously evaluate these methods to en- sure that they are best suited for the project. All teams within the organizations should also be given autonomy to a predefined extent. Through this, many of the problems arising from the collision between the stability needed for cooperation and the flexibility needed for agility should be mitigated.
Keywords: agile; inter-organizational agility; arge-scale agile; cooperation; team autonomy; communication; organizational alignment; culture; flexibility